1999
DOI: 10.1017/s1368980099000373
|View full text |Cite
|
Sign up to set email alerts
|

Supermarket sales data: a tool for measuring regional differences in dietary habits

Abstract: Objective: To assess how well supermarket sales data from a major supermarket chain can reflect on regional differences in dietary behaviour by comparing the sales data with the results provided by the annual health behaviour surveys. Design: Cross-sectional observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…A recent study in Finland has shown similarity between regional sales of dairy products, fats and oils, and reported dietary habits of adult populations 16 . For the majority of the UK, supermarkets dominate the supply of domestic food and as such have a key influence on the nutritional content of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Finland has shown similarity between regional sales of dairy products, fats and oils, and reported dietary habits of adult populations 16 . For the majority of the UK, supermarkets dominate the supply of domestic food and as such have a key influence on the nutritional content of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…23,37 In this way, detailed information available from sales data can be used to detect the differences in the diets of different population groups. For example, seven studies in this review found ethnic, regional, and income differences in population dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…First, generalizability is a concern because in the studies reviewed, data coverage was frequently limited to a handful of stores and households and specific food items. Kirlin et al 23 and Närhi-nen et al 37 reported difficulty in gaining support from retailers to provide sales data routinely because the data were confidential. Additional work is required to explore feasible ways to get national data coverage by increasing the accessibility of sales data and reducing cost and access barriers, for example, by exploring ways to get retailer support and working with local market research companies to identify ways to obtain scanner data sets suitable for long-term nutritional surveillance at a favorable price.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supermarket sales data have been used for a variety of purposes, including testing interventions that promote healthier food choices [6][7][8][9] , understanding determinants of food purchasing behaviour 10,11 , measuring regional differences in dietary habits 12,13 and as an index of nutrient intake in a population who buy most of their food from supermarkets 14 .…”
mentioning
confidence: 99%